La production des savoirs sur les pesticides dans la règlementation européenne - Annie Martin (VertigO)
This article presents a critical approach of the European rules of knowledge production on the harmful effects of plant protection products. We borrow the theorical framework from sociology, agnotology, to show that the lack of awareness of the origin of the European rules and their legal nature, are factors explaining that teir content causes a production of ignorance about harmful effects of pesticides. Indeed, the European rules of knowledge production are the result of a phenomenon of dissemination of norms between Organisation for Economic Co-operation and Development and European Union since the early 1970s. This characteristic of european rules, unknown to academic legal literature is all the more invisible that the transfer of norms is made by many technical texts pertaining to soft law and hard law. The content of european law confirms that they result in a production of ignorance at two levels : the harmonized criteria of harmfulness, decisive to ban the access to the market are incomplete and can be ruled out by many derogations ; rules announce the production of knowledges on three categories of substances taken individually, but only one of them is the object of an evaluation, whereas the rules of identification of the risks relative to cumulative effects do not exist yet.